The Pros and Cons of the “New Normal” Concept during COVID-19 Outbreak - Nadi Suprapto; Akhmad Zamroni; Azmil Abidah; Desi Wulandari (STAI Miftahul Ula Nganjuk, 2021)
This position paper narrates how the author's position based on the hot issue of nurturing the COVID-19 pandemic. The pros and cons of the